The measurement of human motion: A comparison of commercially available systems - Richards, J. G. (Human Movement Science, 1998)
This experiment to compare the available motion analysis system was conducted by Dr. James G. Richards, Ph.D. from the University of Delaware, Newark DE. Dr. Richards was assigned the task to compare as objectively as possible all the existing motion analysis systems and present it at the 3D Conference of Human Movement. The 3D conference is an official function of the International Society of Biomechanics (ISB) and is considered to be the most credible and influential in the field of Biomechanics. The experiment was conducted and the results of this study were presented with no interference from the companies whose products were tested. Dr. Richards selected customers sites to conduct the experiment. In a few cases, such as with Elite and CODA, results were returned to the companies' headquarters to determine the source for the results which were accessibly inaccurate. The results of this study were presented at the 3D Conference of Human Movement at the University of Tennessee, Chattanooga, Tennessee. July 3rd, 1998. The title of Dr. Richards' paper was: "The Measurement of Human Motion: A Comparison of Commercially Available Systems." The article published in the Proceedings were only some preliminary results and many of these findings were incorrect. The correct, up-to-date results were presented during the oral presentation and in the final paper by Dr. Richards. The clarification of results between the preliminary, pre-Conference publication and the appropriate, up-to-date results were particularly important for a video based system such as the APAS system. For the APAS system, the initial results were based on data obtained from only 2 cameras which was inappropriate for an experiment utilizing the experimental test device. The test device had a mechanical arm which rotated 360 degrees and, therefore, obviously required a minimum of 5 cameras in order to see each marker from at least two cameras views. Restricting the data collection to only two cameras created some peculiar situations such that nearly 176 degrees of motion were detected by one only camera, 112 degrees by two cameras, and the remaining degrees were undetected by any camera. Because of the specific conditions inherent with this test device, the experiment had to be repeated utilizing 5 cameras. All other venders used 6 cameras. The final paper that was presented, included 5 cameras which is the only way to be able to analyze this particular device. All the other companies used 6 cameras and even using 6 cameras, two of the companies could not produce reliable and valid results. However, with normal, straightforward experimental testing of human movement, three cameras and, frequently only two cameras, are adequate with the APAS system.